One year in Coal Harbor - Horvath, Polly (Schwartz & Wade Books, 2012)
In a small fishing village in British Columbia, twelve-year-old Primrose tries to be a matchmaker for her Uncle Jack, befriends Ked, a new foster child, tries to decide if she is willing to go to jail for her convictions, and together with Ked, publishes a cook book to raise money for the Fisherman's Aid. Includes recipes.